The Role of Self-Efficacy in Treatment Adherence and Quality of Life Improvement in Hypertensive Patients - Dewi, Aulia Kusuma; Maliya, Arina (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Hypertension is a global health problem that affects quality of life, morbidity, and mortality, with low self-efficacy and poor medication adherence being major barriers to effective management. Objectives: This study aimed to analyze the relationship between self-efficacy, medication adherence, and quality of life among hypertensive patients. Methods: A cross-sectional study was conducted at the Kartasura Health Center from June to November 2024 involving 128 purposively selected respondents. Data were collected using a structured questionnaire and analyzed using statistical tests to determine variable relationships. Results: Most respondents demonstrated low self-efficacy, poor medication adherence, and low quality of life; the majority were females aged 56–65 years with junior high school education. Statistical analysis revealed a significant relationship between self-efficacy and treatment adherence (p < 0.001), as well as between self-efficacy and quality of life (p = 0.002). Furthermore, patients with higher self-efficacy scores exhibited 1.8 times greater adherence and 1.6 times higher quality of life scores compared to those with lower self-efficacy. Conclusion: Self-efficacy plays a pivotal role in enhancing medication adherence and quality of life among hypertensive patients; thus, interventions aimed at strengthening self-efficacy should be prioritized in hypertension management programs.